DATA ANALYSIS BY FORMAL METHODS OF ESTIMATION OF INDEXES OF RATING CRITERION IN PROCESS OF ACCUMULATION OF DATA ABOUT WORKING OF THE TEACHING STAFF - Alexey E. Fedoseev (Статистика и экономика)
The article considers the development of formal methods of assessing the rating criterion exponents. The article deals with the mathematical model, which allows to connect together quantitative rating criterion characteristics, measured in various scales, with intuitive idea of them. The solution to the problem of rating criterion estimation is proposed.